Calappidae de Haan 1833 - González, José A. (Zenodo, 2018)
Calappidae de Haan, 1833 Calappa galloides Stimpson, 1859 —CNI González et al. (2000); 15–80 m—CVI Miers (1886, as C. gallus ); 0–80 m—Benthic, 12– 218 m. AAWA. Calappa granulata (Linnaeus, 1758) —CNI Brullé (1839); 15–300 m—CVI A. Milne-Edwards & Bouvier (1900); 75–233 m—Benthic, 10– 400 m. ATLM. Calappa spec. Fransen, 1991 —CNI type-locality; 45–80 m (also in Salvage Islands, 192 m);— CVI Fransen (1991); 92 m—Benthic, 80–192 m. ECAI. Cryptosoma cristatum Brullé, 1837 —CNI type-locality (as C. cristata ); 2–89 m—CVI Lucas (1882); Türkay (1982, as Cycloes cristata ); 40–50 m—Benthic, 2– 75 m. ECAI. : Published as part of González, José A., 2018, Checklists of Crustacea Decapoda from the Canary and Cape Verde Islands, with an assessment of Macaronesian and Cape Verde biogeographic marine ecoregions, pp. 401-448 in Zootaxa 4413 (3) on page 421, DOI: 10.11646/zootaxa.4413.3.1, http://zenodo.org/record/3769606 : {"references": ["Gonzalez, J. A., Quiles, J. A. & Santana, J. I. (2000) The family Calappidae (Decapoda, Brachyura) around the Canary Islands. Crustaceana, 73, 1007 - 1014.", "Miers, E. J. (1886) Report on the Brachyura collected by H. M. S. Challenger during the years 1873 - 76. Report on the Scientific Results of the Voyage of H. M. S. \" Challenger \" during the years 1873 - 76, Zoology, 17, i-xli + 1 - 362.", "Milne-Edwards, A. & Bouvier, E. L. (1900) Brachyures et Anomoures. In: Crustaces Decapodes, Premiere Partie. Expedition scientific Travailleur et Talisman, 6, 1 - 396. [Paris]", "Fransen, C. H. J. M. (1991) Preliminary report on Crustacea collected in the eastern part of the North Atlantic during the CANCAP and MAURITANIA Expeditions of the former Rijksmuseum van Natuurlijke Historie, Leiden. Nationaal Natuurhistorisch Museum, Leiden, vi + 200 pp.", "Brulle, M. (1837 - 1839) Crustaces. In: Webb, P. B. & Berthelot, S. (Eds.), Histoire naturelle des Iles Canaries, Zoologie, 2 (2: Entomologie), Paris, pp. 13 - 18, 1 pl. (Crustaces). [Atlas (1837); Text (1839)]", "Lucas, H. (1882) Note sur un Crustace Brachyure de la famille des Calappiens. Annales de la Societe entomologique de France, Serie 6, 2, 115.", "Turkay, M. (1982) Marine Crustacea Decapoda von den Kapverdischen Inseln mit Bemerkungen zur Zoogeographie des Gebietes. Courier Forschungsinstitut Senckenberg, 52, 91 - 129."]}